Impact-induced bubble interactions and coalescence in soft materials. (1st March 2022) - Fu, Yimou; Hu, Xiaocheng; Liu, Yide; Wang, Peng; Chen, Shuo; Zhou, Haofei; Yu, Honghui; Qu, Shaoxing; Yang, Wei
Abstract: Cavitation in soft materials attracts many attentions due to its importance for a range of biomedical problems and applications, such as cavitation-induced traumatic brain injury, high-intensity focused ultrasound lithotripsy, and the treatment of tumors. However, existing studies are mainly focused on the deformation behavior of a single bubble. The dynamic configuration and the failure process of multiple bubble interactions, which are significantly different from those of a single bubble, remain largely unknown. Here, we performed experimental and analytical studies to investigate the impact-induced interactions of bubbles in soft materials, where bubbles of controllable size and spacing were introduced with the aid of a highly efficient rheology modifier, namely carbomer. A drop tower system paired with a high-speed camera was utilized to conduct impact tests and concurrently visualize the evolution of the bubble configuration. A theoretical model containing pressure radiated by bubbles is proposed to predict the spherically symmetric deformation of multi-bubble interactions, as well as the inhibition between bubbles during deformation. A combination of energy-based strength theory and finite element analysis is used to reveal the squeeze and coalescence mechanisms of the bubbles. The failure of soft material is shown to depend on stress triaxiality; in particular, the material can rupture at unloading and under a stress lower than the historic maximum. A phase diagram was drawn to predict the critical impact loads for bubble coalescence at different conditions. Our work provides a promising clue to the understandings for the interactions and coalescence behavior of bubbles those ubiquitously exist in natural and artificial soft materials.